Impact of Vehicle Type and Road Quality on Cargo Securing - Martin Vlkovsky (Communications - Scientific letters of the University of Zilina, 2020)
The article is concerned with comparison of the three transportation experiments using the two vehicle types (Tatra 810 and Tatra 815 MK IV) on two road types (higher and lower quality). From the transportation experiments, three datasets were obtained to be compared mutually and to the normatively determined values of acceleration coefficients, as well. In the article, the calculation of the probability of excess and double excess of the normatively determined limits is also included. For the purpose of the comparison, statistical tests of equality and three different parameters are employed. Statistically significant differences between the datasets are the outcome of the article, i.e. there are statistically significant differences between the vehicles and roads tested with regard to generated shocks. The results are primarily usable in the cargo securing system optimisation in road transportation and transport safety.